A Brain for Business - A Brain for Life How insights from behavioural and brain science can change business and business practice for the better - O'Mara, Shane (The Neuroscience of Business, 2018)
Behaviour change is hard, but O'Mara shows that by adopting strategies that are well-founded in the science of brain and behaviour individuals and organisations can adapt to the demands of the modern world. The brain matters in business. The problem is that our brains have many biases, heuristics and predilections that can distort behaviour and decision making. The good news is that we know more about how these work than ever before. O'Mara's starting point is that, as our behaviour arises from the structure and function of our brains, careful examination of a series of brain-based ('neurocognitive') analyses of common aspects of human behaviour relevant to business and management practice reveals lessons that can be used at work. He begins by looking at neuroplasticity and how it is enables a shift from a restrictive 'fixed mindset' to an enabling 'growth mindset'. He shows how this changing mindset approach - where the focus is on task and improvements based on effort - is scalable within organisations. Next, as the brain is a living organ like the heart and lungs, O'Mara shows how to keep it physically in the best possible shape before examining how we exercise control over our behaviour, build resilience and create positive brain states. He also considers the implications for business of our brains wiring for status and illustrates how research shows that it is possible to de-bias assumptions about gender and race - and the impact that this has on performance.